A manufacturable platform for photonic quantum computing - Koen Alexander; Avishai Benyamini; Dylan Black; Damien Bonneau; Stanley Burgos; Ben Burridge; Hugo Cable; Geoff Campbell; Gabriel Catalano; Alejandro Ceballos; Chia-Ming Chang; Sourav Sen Choudhury; et al. (Nature, 2025)
Abstract Although holding great promise for low noise, ease of operation and networking1, useful photonic quantum computing has been precluded by the need for beyond-state-of-the-art components, manufactured by the millions2–6. Here we introduce a manufacturable platform7 for quantum computing with photons. We benchmark a set of monolithically integrated silicon-photonics-based modules to generate, manipulate, network and detect heralded photonic qubits, demonstrating dual-rail photonic qubits with 99.98% ± 0.01% state preparation and measurement fidelity, Hong–Ou–Mandel (HOM) quantum interference between independent photon sources with 99.50% ± 0.25% visibility, two-qubit fusion with 99.22% ± 0.12% fidelity and a chip-to-chip qubit interconnect with 99.72% ± 0.04% fidelity, conditional on photon detection and not accounting for loss. We preview a selection of next-generation technologies: low-loss silicon nitride (SiN) waveguides and components to address loss, as well as fabrication-tolerant photon sources, high-efficiency photon-number-resolving detectors (PNRDs), low-loss chip-to-fibre coupling and barium titanate (BTO) electro-optic phase shifters for high-performance fast switching.